Factors associated with the acceptability of mass drug administration for filariasis: a systematic review - Abdul Halim, Ahmad Farid Nazmi; Ahmad, Dzulfitree; Ling, Jane Miaw Yn; Masdor, Noor Azreen; Ramly, Nurfatehar; Othman, Rahayu; Kandayah, Thinakaran; Hassan, Mohd Rohaizat; Dapari, Rahmat (Multidisciplinary Digital Publishing Institute, 2022)
Mass drug administration (MDA) has been implemented as a tool to eliminate lymphatic filariasis. Acceptability among susceptible populations is crucial to achieving MDA effective coverage. This systematic review aims to present and systematically determine the factors associated with the acceptability of MDA. Articles related to factors associated with acceptability were collected electronically from three different databases (Scopus, Web of Science, and PubMed). Four pairs of independent reviewers screened the titles and abstracts of the collected data, stored in EndnoteX7, against the inclusion criteria. Afterwards, the included articles have been critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Of the 68 articles identified, 11 were included in the final review. Knowledge, awareness, attitude and perceptions, communications, delivery and accessibility of MDA, gender, and age are the factors associated with MDA acceptability. Community acceptance remains a challenge in the implementation of MDA. To expand MDA coverage in all endemic countries, there is a strong need to address the factors influencing community acceptance of MDA.